Biblioterapi Untuk Mengurangi Kecemasan Santri - Hulyatuzzahroh , Richa; Al Musafiri, M Rizqon (Program Studi Bimbingan dan Konseling Islam, 2023)
Research with a background of anxiety experienced by Santri Pondok Pesantren Darussalam including the absence of Maulid Holidays, and the number of activities. With that, students experience anxiety with the criteria: feeling anxious, moody, lazy to study, not focused, worried, bored and some even intend to leave campus without permission. Seeing the background and the existence of qanuns, the researcher suggests applying Bibliotherapy techniques. Bibliotherapy is also known as the book reading technique. According to Herlina stated, bibliotherapy has benefits including: (1) Helping patients gain understanding, (2) Providing relaxation and diversion techniques, (3) Helping sufferers to focus more. The type of research used is descriptive qualitative. Data collection methods: observation, interviews and documentation. Bibliotherapy technique stage: good report card, book identification, book introduction, follow-up strategy, and evaluation. This research shows the benefits that readers get: Helping sufferers gain understanding, relaxation and diversion techniques, Helping to be more focused, forming a positive self-concept, understanding behavior, easing emotions, increasing compassion, and developing empathy and self-awareness.